2019
DOI: 10.18231/j.ijooo.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

To study the efficacy of air descemetopexy in the management of various types of descemet membrane detachment based on anterior segment – optical coherence tomography & to know the role of other gases Perfluoropropane (14% C3F8) and sulphur hexafluoride (20% SF6) in failed cases of air descemetopexy

Abstract: Purpose: To study the efficacy of air descemetopexy in the management of various types of descemet membrane detachment (DMD). Materials and Methods: After ethical committee approval, clinical data of 40 patients during the period of December 2017 to December 2018, who developed DMD after cataract surgery were analysed. Results: Majority of patients (n= 32, 80%) had severe generalized corneal edema, n = 4 had moderated corneal edema & n = 4 had localized mild corneal edema. Only air was sufficient to reattach D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Since then, both air and SF 6 have been used widely but no strong evidence supports what is the more appropriated gas to deal with DMD. Chaurasia et al and Singh et al have suggested air descemetopexy as a safe treatment option for DMD in most patients [11,12]; however, some researchers prefer the long-lasting effect of SF 6 descemetopexy [1,13]. Air resolution occurs within 3-4 days and might not be long enough for reattachment of the DM.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, both air and SF 6 have been used widely but no strong evidence supports what is the more appropriated gas to deal with DMD. Chaurasia et al and Singh et al have suggested air descemetopexy as a safe treatment option for DMD in most patients [11,12]; however, some researchers prefer the long-lasting effect of SF 6 descemetopexy [1,13]. Air resolution occurs within 3-4 days and might not be long enough for reattachment of the DM.…”
Section: Introductionmentioning
confidence: 99%